A new technique of real-time monitoring of fiber optic cable networks transmission - Bakar A.A.A.; Jamaludin M.Z.; Abdullah F.; Yaacob M.H.; Mahdi M.A.; Abdullah M.K. (2023)
A new technique of fiber-break detecting and monitoring in optical communication network systems is proposed and experimentally demonstrated. The subsystem, namely fiber-break monitoring system is designed to be simpler, significantly less expensive and yet gives an appropriate measurement to the distance break in place of the optical time domain reflectometer. This new approach has a bright prospect to be utilized in existing optical communication network systems. The proposed technique gives a minimal insertion loss of 1.7 dB and measurement accuracy of 0.285 km. 2006 Elsevier Ltd. All rights reserved.